Growth and Carcass Characteristics of Japanese Quails Fed Diets Containing Varying Levels of Moringa Leaf Meal - Varalakshmi, G; Kishore, K Raja; Kumar, D Srinivas; Seshaiah, Chappidi Venkata (Indian Journal of Animal Nutrition, 2021)
The present experiment was conducted to evaluate the effect of incorporation of Moringa Leaf Meal (MLM) in the diet on growth and carcass characteristics of Japanese quails. One hundred and fifty day-old chicks were randomly allotted to five dietary treatment groups with three replicates of 10 birds each for 5 weeks. Moringa leaves were dried, ground and incorporated at 0 (T1; Control), 1.5% (T2), 3.0% (T3), 4.5% (T4) and 6.0% (T5) per cent levels, respectively, in iso-caloric and iso-nitrogenous broiler quail diets to meet the requirements as per NRC (1994). Results indicated a significant increase (P